Investigation of the effect of various pretreatments on the freeze-drying process of blue mussel (Mytilus edulis) - Alp, Nurgul; Ozyalcin, Zehra; Kipcak, Azmi (EGE UNIV, FAC FISHERIES, 2025)
In this study, freeze-drying of blue mussels with various pretreatments was investigated, the effective moisture diffusion value was determined, and mathematical models were applied to the drying data. Pretreatments were applied as: 1- and 5-min ultrasonication (US), 30- and 60-sec blanching (BW), 30- and 60-sec blanching in 10% salt water (BSW); 1- and 5-min osmotic dehydration (OD)in 10% salt water and 1- and 5-min OD in 20% salt water. Blue mussel samples were freeze-dried until the final moisture content dropped below 7%. The OD pretreatment provided the lowest final moisture content, while the BW had the highest final product moisture content. The highest coefficient of determination (R2), the lowest root mean square error (RMSE), and reduced chisquare (chi 2) values were used to select the most appropriate mathematical model. The best fitting mathematical models were Alibas, Midilli & Kucuk, and two- term exponential.
Keywords: Blue mussel; Mytilus edulis; freeze-drying; lyophilization; mathematical modelling; KINETICS; Fisheries; Marine & Freshwater Biology